2019
DOI: 10.1097/01.jaa.0000586332.19619.b6
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction and workplace stressors among surgical providers at a single institution

Abstract: Objective: Job satisfaction and work stress are associated with provider health and patient outcomes. This study aimed to evaluate job satisfaction and workplace stressors in surgical providers (surgeons, physician assistants [PAs], and NPs). Methods: A survey was distributed to providers within a single surgical department. Job satisfaction and workplace stressors were evaluated by sex, age, profession, career length, and work hours. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…In contrast to our study, Joanna Kobza did a study among dentists found job satisfaction decreased with increased age [13]. Rebecca Gates and Mubashir Baig Mirza found no significant difference between age and job satisfaction [14,15].…”
Section: Key Findingscontrasting
confidence: 94%
See 1 more Smart Citation
“…In contrast to our study, Joanna Kobza did a study among dentists found job satisfaction decreased with increased age [13]. Rebecca Gates and Mubashir Baig Mirza found no significant difference between age and job satisfaction [14,15].…”
Section: Key Findingscontrasting
confidence: 94%
“…Rebecca Gates study showed providers working 11 to 15 years had higher job satisfaction [14]. Doaa M. Abdel-Salam and Nabila S. Ben Slimane showed no significant difference between job satisfaction and years of experience [16,22].…”
Section: Key Findingsmentioning
confidence: 99%
“…Burnout is characterized by emotional exhaustion, depersonalization, and loss of self-worth [31]. Up to 50% of doctors and nurses report symptoms of burnout [32][33][34] with health care organizations cited as a leading cause [35][36][37][38][39][40]. In this longitudinal prospective survey-based study of healthcare workers during the COVID-19 pandemic, higher POS was associated with lower anxiety and risk for burnout.…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have demonstrated that providers frequently cite organizational causes of burnout [3,[36][37][38][39][40]; characteristics of the person may also contribute to burnout during periods of crisis [43]. We identified several individual factors that were associated with risk for burnout.…”
Section: Plos Onementioning
confidence: 93%